Implementasi Program Tahsin Dengan Metode Usmani Di Masjid Al-Ikhlas Sambilegi Lor - Riki Herman; Muhammad Rizki (PT. Nawa Edukasi Nusantara, 2025)
Tahsin Program with the Usmani Method of Al-Ikhlas Mosque Sambilegi-Lor Maguwoharjo Depok Sleman Yogyakarta, Reading the Qur'an correctly as revealed is the obligation of every Muslim and Muslim woman, but the ability of the majority of Muslims is still concerning, this can be seen from the low level of public engagement with the Qur'an and many factors that cause this situation, including teaching methods that are less manhaji, inadequate teachers or less aware individuals weakness in the Tajwidul Qur'an so that we are not interested in teaching, whatever the obvious reason we still believe in the wisdom of Allah